Efficient and Stable 3D/2D Perovskite Solar Cells through Vertical Heterostructures with (BA)4AgBiBr8 Nanosheets. Issue 39 (26th August 2022) - Zhao, Dan; Gao, Danpeng; Wu, Xin; Li, Bo; Zhang, Shoufeng; Li, Zhen; Wang, Qi; Wu, Zongxiao; Zhang, Chunlei; Choy, Wallace C. H.; Zhong, Xiaoyan; He, Qiyuan; et al.
Abstract: Perovskite solar cells (PVSCs) have drawn great attention due to their high processability and superior photovoltaic properties. However, their further development is often hindered by severe nonradiative recombination at interfaces that decreases power conversion efficiency (PCE). To this end, a facile strategy to construct a 3D/2D vertical heterostructure to reduce the energy loss in PVSCs is developed. The heterostructure is contrived through the van der Waals integration of 2D perovskite ((BA)4 AgBiBr8 ) nanosheets onto the surface of 3D‐FAPbI3 ‐based perovskites. The large bandgap of (BA)4 AgBiBr8 enables the formation of type‐I heterojunction with 3D‐FAPbI3 ‐based perovskites, which serves as a barrier to suppress the trap‐assisted recombination at the interface. As a result, a satisfying PCE of 24.48% is achieved with an improved open‐circuit voltage ( V OC ) from 1.13 to 1.17 V. Moreover, the 2D perovskite nanosheets can effectively mitigate the iodide ion diffusion from perovskite to the metal electrode, hence enhancing the device stability. 3D/2D architectured devices retain ≈90% of their initial PCE under continuous illumination or heating after 1000 h, which are superior to 3D‐based devices. This work provides an effective and controllable strategy to construct 3D/2D vertical heterostructure to simultaneously boost the efficiency and stability of PVSCs. Abstract : (BA)4 AgBiBr8 2D perovskite nanosheets are used to construct vertical heterostructures with 3D perovskite to serve as a barrier layer to suppress the ion diffusion and nonradiation recombination from 3D perovskite to metal electrode. The performance and stability of perovskite solar cells are simultaneously enhanced after the incorporation of the 2D nanosheets.